Design and implementation of a device-independent system for adaptive composition of web services. (9th May 2006) - Mahmoud, Qusay H.; Zahreddine, Wassam
The modularity of web services has left an open problem in composition – a scenario that involves an amalgamation of two or more web services to fulfil a request that no one web service is able to provide. This paper presents the design and implementation of a system that enables users of any device to dynamically discover context-based web services that will be automatically composed to satisfy a user's request. Existing web services can be easily adapted and new web services can be easily deployed. The system uses a custom UDDI-like registry that we have designed and implemented to support context-based adaptive composition.